Oblique evanescent excitation of a dielectric strip: A model resonator with an open optical cavity of unlimited Q - Hammer, Manfred; Ebers, Lena; Förstner, Jens (Optics Express)
A rectangular dielectric strip at some distance above an optical slab waveguide is being considered, for evanescent excitation of the strip through the semi-guided waves supported by the slab, at specific oblique angles. The 2.5-D configuration shows resonant transmission properties with respect to variations of the angle of incidence, or of the excitation frequency, respectively. The strength of the interaction can be controlled by the gap between strip and slab. For increasing distance, our simulations predict resonant states with unit extremal reflectance of an angular or spectral width that tends to zero, i.e. resonances with a Q-factor that tends to infinity, while the resonance position approaches the level of the guided mode of the strip. This exceptionally simple system realizes what might be termed a “bound state coupled to the continuum”.
Keywords: tet_topic_waveguides

Sonderpädagogik als Erfahrungs- und Praxiswissenschaft. Geistes-, sozial- und kulturwissenschaftliche Perspektive - Dederich, M; Ellinger, S.; Laubenstein, Désirée

Beurteilung der Leistungsfähigkeit von Schmierstoffen mittels eines FZG Prüfstandes - Keßler, A; Elkenkamp, P; Magyar, Balázs; Mayer, C (Tribologie und Schmierungstechnik)

Teamentwicklung und Teamkooperation - Guthöhrlein, K.; Laubenstein, Désirée; Lindmeier, C.

Reibenergie basierte Verschleißsimulation für Radialwellendichtringe - Foko Foko, F; Sauer, B; Magyar, Balázs

The ‘Learning Office’ as an Approach for Inclusive Education in Mathematics: Opportunities and Challenges - Laubenstein, Désirée; Guthöhrlein, Kirsten; Lindmeier, Christian; Scheer, David; Sponholz, Dirk (In: Kollosche, D.; Marcone, R.; Knigge, M.; Godoy Penteado, M.; Skovsmose, O. (Hrsg.). Inclusive Mathematics Education. State-of-the-Art Research from Brazil and Germany)

Das Praxissemester von angehenden Lehrkräften - Caruso, Carina

Praxissemester (Religion) in NRW: Bilanz und Perspektiven - Caruso, Carina; Woppowa, Jan
Since the winter semester 2014 / 2015 long-term internships have become an integral part of the second master semester at universities in North Rhine-Westphalia. One aim is to improve the development of competencies of prospective teachers. This anthology provides an insight into perspectives of long-term internships in North Rhine-Westphalia referring especially to internships of those prospective teachers, who are going to be teachers for religious education. First Bardo Herzig and Christoph Wiethoff present the plan, the structure and the content of long-term internship at Paderborn University. They take pedagogy as their example. Petra Herzmann and Anke B. Liegmann provide a comprehensive survey of qualitative research on long-term internships and present ideas of a qualitative research programme. Carina Caruso and Andreas Seifert focus on the development of pedagogical knowledge of prospective teachers of religious education during the practice phase. Malte Kling gives a summary of his thesis referring to the change of roles of prospective teachers of religious education. Guido Hunze und Gudrun Lohkemper have a look at the relation between theory and practice for a successful professionalization. Norbert Brieden and Monika Tautz compare the accompaniment of students at Cologne and Wuppertal University and put forward an impetus for teaching at university. Mirjam Zimmermann looks at spirituality in internships. Guido Meyer and Carsten Misera give a definition of heterogeneity as a starting point of the development of the teacher habitus. Christoph Vogelsang and Ulrich Feeser-Lichterfeld contribute to a further combination of perspectives on internships. Carina Caruso and Jan Woppowa give a final summary looking especially at future tasks of the design of long-term internships in theology.

On the nomological net of (non-) workaholic subtypes - Ontrup, Greta; Patrzek, Justine (Career Development International)

Estimation of Nematic Order Parameters via Haller Analysis of 1H NMR Spectra of Liquid Crystals - Tang, Ming-xue; Schmidt, Claudia (Chinese Journal of Magnetic Resonance)
The Haller relationship was applied to estimate the nematic order parameter S from 1H NMR spectra of fully protonated liquid crystals aligned in the magnetic field. The NMR line shapes were approximated as doublets of very broad peaks. Both the temperature-dependent doublet Splitting and the full width at half maximum of the whole spectra were used for Haller extrapolation. The order parameters obtained with the proposed approach for 4-cyano-4'-pentylbiphenyl (5CB) and the nematic mixture E7 were found to be in good agreement with previously reports.
Keywords: nematic liquid crystal; order parameter; Haller analysis; 1H NMR